Conformational pH dependence of intermediate states during oligomerization of the human prion protein. - Gerber, R; Tahiri-Alaoui, A; Hore, P; James, W (2008)
Intermediate states are key to understanding the molecular mechanisms governing protein misfolding. The human prion protein (PrP) can follow various misfolding pathways, and forms a soluble beta-sheet-rich oligomer under acidic, mildly denaturing, high salt conditions. Here we describe a fast conformational switch from the native alpha-monomer to monomeric intermediate states under oligomer-forming conditions, followed by a slower oligomerization process. We observe a pH dependence of the secondary structure of these intermediate forms, with almost native-like alpha-helical secondary structure at pH 4.1 and predominantly beta-sheet characteristics at pH 3.6. NMR spectroscopy differentiates these intermediate states from the native protein and indicates dynamic rearrangements of secondary structure elements characteristic of a molten globule. The alpha-helical intermediate formed at pH 4.1 can convert to the beta-sheet conformation at pH 3.6 but not vice versa, and neither state can be reconverted to an alpha-monomer. The presence of methionine rather than valine at codon 129 accelerates the rate of oligomer formation from the intermediate state.